2006
DOI: 10.1111/j.1445-2197.2006.03762.x
|View full text |Cite
|
Sign up to set email alerts
|

Driving Plastered: Who Does It, Is It Safe and What to Tell Patients

Abstract: According to these results, a doctor's advice should be to patients not to drive in a long arm upper limb fracture cast and to consider concomitant patient factors when advising patients in short arm casts. Although we do not suggest that patients drive while wearing any cast, we have found a large proportion do. Our limited study has found that a young, fit and pain-free person may be able to drive well enough to pass a driving test while wearing a short arm cast.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
47
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(49 citation statements)
references
References 3 publications
1
47
0
1
Order By: Relevance
“…3 Whereas the NHTSA recommendation is to avoid driving with any splint or immobilization device that may interfere with driving, 23 studies have shown that patients often continue to drive despite extremity immobilization. 3,14,15,33 The prevalence of noncompliance clearly indicates the need for evidencebased recommendations for patients whose care involves the use of temporary immobilization devices.…”
Section: Collisionsmentioning
confidence: 99%
See 2 more Smart Citations
“…3 Whereas the NHTSA recommendation is to avoid driving with any splint or immobilization device that may interfere with driving, 23 studies have shown that patients often continue to drive despite extremity immobilization. 3,14,15,33 The prevalence of noncompliance clearly indicates the need for evidencebased recommendations for patients whose care involves the use of temporary immobilization devices.…”
Section: Collisionsmentioning
confidence: 99%
“…There have been few studies examining the effect of upper extremity immobilization on driving performance, with the majority of research focusing on above-and below-the-elbow casts and splints. 4,9,12,14,15 To our knowledge, there has been no study investigating the effect of shoulder immobilization on driving safety. Using a validated computerized driving simulator, this study sought to determine the effect of dominant arm sling immobilization on driving performance with a driving simulator.…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…2 Patients in longarm immobilisation devices should not be allowed to drive. 2,3 The evidence for short arm casts is more ambiguous. 2,3 This study tested the ability to steer in a driving simulator in subjects with a short arm cast.…”
Section: Abstract: Arm Injuries; Automobile Driving; Casts Surgicalmentioning
confidence: 99%
“…However, the majority of these articles were related to medical fields, including studies of occupational therapist driver assessors or associations between driving and illnesses such as dementia; stroke; Parkinson's disease; visual impairment; neurological conditions; orthopaedic issues; sleep problems; attention deficit hyperactivity disorder (ADHD); autism spectrum disorder (ASD); Down's syndrome; and the effect of drugs, medications and alcohol. [20][21][22][23][24][25][26][27][28] The subject population was often composed of older drivers, with the articles focusing on their fitness to drive. Critically, even if PDIs were involved in some articles, they were not the main subjects but were instead contributors, for instance in upholding the research design or its validity and reliability.…”
Section: Methodsmentioning
confidence: 99%